New nexus tool supports holistic management of the Incomati Basin - Velpuri, Naga Manohar; Etichia, Mikiyas; Lautze, Jonathan F. (CGIAR System Organization, 2023)
From its sources in the western mountains and plateau of Mpumalanga in South Africa to its mouth just north of Maputo’s bustling docks in Mozambique, the Incomati River basin supports lives, livelihoods, and irreplaceable ecosystems across eastern Southern Africa. However, growing irrigation and energy needs and accelerating climate change have placed increasing water stress on the transboundary river basin. Without responsive, data-driven, and coordinated management from the basin’s three countries – South Africa, Eswatini, and Mozambique – the lifeblood of the region is at risk of drying up.